Early childhood adversities and risk of eating disorders in women: A Danish register‐based cohort study. Issue 12 (6th November 2017) - Larsen, Janne Tidselbak; Munk‐Olsen, Trine; Bulik, Cynthia M.; Thornton, Laura M.; Koch, Susanne Vinkel; Mortensen, Preben Bo; Petersen, Liselotte
Abstract: Objective: Previous studies evaluating the association between early childhood adversities and eating disorders have yielded conflicting results. The aim of this study is to examine the association between a range of adversities and risk of anorexia nervosa (AN), bulimia nervosa (BN), and eating disorder not otherwise specified (EDNOS) in 495, 244 women. Method: In this nationwide, register‐based cohort study, nine types of early childhood adversity (family disruption, residential instability, placement in out‐of‐home care, familial death, parental somatic illness, parental psychiatric illness, parental disability, severe parental criminality, and parental substance use disorder) were defined and exposure during the first 6 years of life was determined. Hazard ratios for eating disorders were calculated using Cox regression. Results: Few adversities were significantly associated with AN, and for each, the presence of the adversity was associated with lower risk for AN. BN, and EDNOS were positively associated with several types of adversities. AN rates were unchanged or reduced by up to 54% by adversities, whereas rates of BN and EDNOS were unchanged or increased by adversities by up to 49 and 89%, respectively. Discussion: Our findings indicate that childhood adversities appear to be associated with an increased risk of BN and in particular EDNOS, whereas they seem to be either unassociated or associated with a decreased risk of AN.